PsychologicalViolence in Social Media: "Sharing" Culture as Pressure, Exploitation, Threat - Bahar YALIN (Fırat University, 2019)
All humanity is witnessing the spread and diversification of violence in all areas of society. The size of violence grows day by day. These various forms of violence, which are not only exposed by a single gender, continue to affect every age group. One of the concepts of this diversity that adds to the literature is psychological violence, which is defined as pressure, exploitation and threat that are systematically applied to emotions. Social media is the leading of places where psychological violence exists the most. Social media which is defined as an environment and opportunity in our time which is defined as a communication revolution is an environment where becoming different types and dimensions of violence at the social and individual level are different. Today, as social media platforms and the number of users increase and diversity, young people are heavily exposed to the effects of this new and different experience environment while using social media platforms more intensely. Young people who use social media for various purposes are undergoing psychological violence during most of their life, perhaps without realizing it. In this respect, the aim of the study titled "Gender Dimension Psychological Violence in the Social Media" is revealing the social media dimension of psychological violence in the direction of these questions; “the situations of psychological violence exposure of women and men in social media, the effects of psychological violence, psychological violence levels of women and men and What are the differences/similarities as all of these? This study will tell us in striking way in-depth interviews of the psychological violence exposure of young people who study at the university.